2000
DOI: 10.1182/blood.v96.5.1723
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, a new member of the family of soluble defense collagens, negatively regulates the growth of myelomonocytic progenitors and the functions of macrophages

Abstract: We investigated the functions of adiponectin, an adipocyte-specific secretory protein and a new member of the family of soluble defense collagens, in hematopoiesis and immune responses. Adiponectin suppressed colony formation from colony-forming units (CFU)—granulocyte-macrophage, CFU-macrophage, and CFU-granulocyte, whereas it had no effect on that of burst-forming units—erythroid or mixed erythroid-myeloid CFU. In addition, adiponectin inhibited proliferation of 4 of 9 myeloid cell lines but did not suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
374
0
21

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 1,158 publications
(409 citation statements)
references
References 52 publications
14
374
0
21
Order By: Relevance
“…18 We reported previously that adiponectin suppresses macrophage function. 39 In addition, adiponectin suppresses TNF-a, and stimulates IL-10 production in macrophages. 26,40 We reported pre- viously that lack of adiponectin increased serum TNF-a in the CDAA diet-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…18 We reported previously that adiponectin suppresses macrophage function. 39 In addition, adiponectin suppresses TNF-a, and stimulates IL-10 production in macrophages. 26,40 We reported pre- viously that lack of adiponectin increased serum TNF-a in the CDAA diet-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that adiponectin induces apoptosis in breast cancer and myelomonocytic leukemia cell lines; this was mediated by downregulation of antiapoptotic genes such as Bcl-2 and Bcl-xL and upregulation of proapoptotic genes such as Bax and p53. 24,39,40 The reason for different apoptotic response between cancer cells is not clear, which necessitate further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing clinical evidence also links hypoadiponectinemia to the development of metabolic syndrome and atherosclerosis (8)(9)(10)(11)(12). Gain-or loss-of-function experiments in mice have suggested that adiponectin is a multifunctional protein that displays antiatherosclerotic (13)(14)(15), antidiabetic (16)(17)(18), anti-inflammatory (19), and antifibrotic properties (20,21), among others.…”
mentioning
confidence: 99%